PENGARUH ARUS KAS BEBAS TERHADAP NILAI PERUSAHAAN DIMEDIASI MANAJEMEN LABA - Harijanto, Victor Aquino; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to test the influence of free cash flow to the earnings management, the influence ofearnings management to the corporate value, and the influence of free cash flow to the corporate value, and alsoto find out whether the influence of free cash flow to the corporate value has mediated by the earningsmanagement. The population of this research is all manufacturing companies of industrial sector of consumergoods which are listed in Indonesia Stock Exchange in 2011-2014 periods. The sample collection has been doneby using purposive sampling technique therefore 16 companies have been selected. The data analysis has beencarried out by using simple linear regressions, multiple linear regressions and path analysis in order to detectthe indirect influence through earnings management. Based on the result of the research, it can be concludedthat free cash flow has negative influence to the earnings management, earnings management has positiveinfluence to the corporate value, and free cash flow has positive influence to the corporate value, earningsmanagement does not mediate the correlation of free cash flow to the corporate value because the directinfluence is greater that indirect influence.Keywords: free cash flow, earnings management, corporate value.